2005
DOI: 10.1073/pnas.0405067102
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of insulin and liver X receptor in the induction and cleavage of sterol regulatory elementbinding protein-1c

Abstract: Sterol regulatory element-binding proteins (SREBPs) are transcription factors central to the regulation of lipid metabolism. The SREBPs are synthesized as precursor proteins that require proteolytic processing to become transcriptionally active. Whereas the regulation of SREBP-1a and -2 cleavage by cellular sterol content is well defined, much less is known about the regulation of SREBP-1c, the predominant SREBP isoform in the liver. Both insulin and liver X receptor ␣ (LXR␣) induce SREBP-1c transcription; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
130
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 42 publications
13
130
2
4
Order By: Relevance
“…9 Our results show that SREBP-1c mRNA expression is increased in the jejunum of morbidly obese subjects with a high insulin resistance, as is also shown in insulin-resistant animals. 10 This increased expression may have resulted from the increased insulinemia, 33 as our results also suggest. Using different multiple regression models, we also found that both, SREBP-1c and/or insulin might be involved in the explanation of mRNA levels of ACC1, MTTP, DGAT2, PDHB, apo A-IV, and FAS.…”
Section: (Fas) (F) Apolipoprotein A-iv (Apo A-iv) (G) Diacylglycerosupporting
confidence: 53%
See 2 more Smart Citations
“…9 Our results show that SREBP-1c mRNA expression is increased in the jejunum of morbidly obese subjects with a high insulin resistance, as is also shown in insulin-resistant animals. 10 This increased expression may have resulted from the increased insulinemia, 33 as our results also suggest. Using different multiple regression models, we also found that both, SREBP-1c and/or insulin might be involved in the explanation of mRNA levels of ACC1, MTTP, DGAT2, PDHB, apo A-IV, and FAS.…”
Section: (Fas) (F) Apolipoprotein A-iv (Apo A-iv) (G) Diacylglycerosupporting
confidence: 53%
“…Using different multiple regression models, we also found that both, SREBP-1c and/or insulin might be involved in the explanation of mRNA levels of ACC1, MTTP, DGAT2, PDHB, apo A-IV, and FAS. It is known that SREBP-1c can regulate ACC1, FAS, and MTTP, 9,34,35 and insulin can regulate SREBP-1c, 33 FAS, 36 apo A-IV, 37 and DGAT2. 38 Therefore, insulin may be involved in the regulation of these genes, directly or through SREBP-1c.…”
Section: (Fas) (F) Apolipoprotein A-iv (Apo A-iv) (G) Diacylglyceromentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report [18] described a central role for LXR in insulin-mediated activation of SREBP-1c transcription and stimulation of fatty acid synthesis in liver. Interestingly, the activation of LXR by TO-901317 leads to the induction of SREBP-1c expression and precursor protein, but not of its mature nuclear form [19]. The LXR-induced SREBP-1c precursor, however, is rapidly cleaved on acute exposure to insulin via a phosphatidylinositol 3-kinase-dependent mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…However, because the amounts of SREBP-1c mRNA and precursor protein were also increased by insulin, whether there was an active effect of insulin on the maturation of SREBP was not clear. More recent studies suggest insulin enhances the hepatic processing of SREBP-1c (Hegarty et al 2005). Insulin signaling activates AKT, which has been reported to be directly involved in the movement of SREBP-SCAP from the ER to Golgi ( Fig.…”
Section: Srebp Regulation By Insulinmentioning
confidence: 99%